2022
DOI: 10.1371/journal.pone.0275349
|View full text |Cite
|
Sign up to set email alerts
|

Pooled prevalence and associated factors of pregnancy termination among youth aged 15–24 year women in East Africa: Multilevel level analysis

Abstract: Background Most of unwanted pregnancies among adolescent girls and young women (AGYW) in Africa result in pregnancy termination. Despite attempts to enhance maternal health care service utilization, unsafe abortion remains the leading cause of maternal death in Sub-Saharan Africa (SSA), there is still a study gap, notably in East Africa, where community-level issues are not studied. Therefore, this study aimed to assess pooled prevalence pregnancy termination and associated factors among youth (15–24 year-old)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 42 publications
1
3
0
Order By: Relevance
“…Our meta-regression analysis showed that women with primary and secondary education were 3 times more likely to undergo induced abortion than their counter parts. This finding is consistent with studies conducted in East Africa, Sierra Leone, Iran, and Nepal [ 68 , 70 , 72 , 78 ]. However, there is a contrary finding from a study conducted in China [ 79 ], which reported a lower prevalence of induced abortion among women with higher educational status.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Our meta-regression analysis showed that women with primary and secondary education were 3 times more likely to undergo induced abortion than their counter parts. This finding is consistent with studies conducted in East Africa, Sierra Leone, Iran, and Nepal [ 68 , 70 , 72 , 78 ]. However, there is a contrary finding from a study conducted in China [ 79 ], which reported a lower prevalence of induced abortion among women with higher educational status.…”
Section: Discussionsupporting
confidence: 93%
“…In this study, unmarried women were 4.49 times more likely to develop induced abortion than their counter part. Studies conducted in East Africa, Sierra Leone, and China have reported contrary result [ 68 , 70 , 79 ]. The discrepancy could be the cultural and social norms surrounding marriage and sexuality in these different regions.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Globally, between 2015 to 2019, it was estimated that 121 million unplanned pregnancies occurred per year. About 60% of the unplanned pregnancies and 29% of all pregnancies were terminated (Hailegebreal, Enyew, Simegn, Seboka, Gilano, Kassa, et al 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Nearly half (45.2%) of all pregnancy terminations occurred in the Highlands region. Women aged [35][36][37][38][39][40][41][42][43][44], not working (aOR = 6.17; 95% CI: 2.26-16.85), owned a mobile phone (aOR = 3.77; 95% CI: 1.60-8.84), and lived in urban areas (aOR = 5.66; 95% CI: 1.91-16.81) were more likely to terminate a pregnancy. Women who experienced intimate partner violence (IPV) were 2.27 times (aOR = 2.27; 95% CI: 1.17-4.41) more likely to terminate a pregnancy compared to those who did not experience IPV.…”
mentioning
confidence: 99%